Religion as a Reconciling Element in Greek-Bulgarian Relations during the First Balkan War (1912) - Stamatia Fotiadou (Zeszyty Cyrylo-Metodiańskie)
From the mid-19th century, Greek-Bulgarian relations are often portrayed as a continuous narrative of rivalry and dispute. Until then, Greeks and Bulgarians belonged to the multiethnic Orthodox millet and used to perceive each other as allies in their struggle to liberate the oppressed brethren. The waning importance of religious collectivity and the rise of national identity in the Balkans contributed to shaping the image of the hostile national Other. As a consequence, differing attempts to legitimize national claims over future control of Ottoman provinces appeared. The first Balkan War in 1912, however, witnessed a resurgence of religious unity that dominated national narratives, thus reconstructing negative stereotypes of the Other. Within a Balkan war alliance, the Greek and Bulgarian press emphasized Orthodox Christian unity between the two peoples as a motive to fight against Ottoman dominance. This paper examines how Greek and Bulgarian newspapers changed their content during the war of 1912–1913, emphasizing religion as the missing link between the two nations. Original title in Bulgarian: Религията като обединяващ елемент в гръцко-българските отношения по време на Първата балканска война (1912 г.)